Efecto de los azúcares reductores en la producción de polihidroxialcanoatos a partir de hidrolizados de citrus nobilis empleando bacillus sp - Castro Benites, Betty Maria (2019)
In this research work, the effect of reducing sugars on the production of polyhydroxyalkanoates from Citrus Nobilis hydrolyzate using Bacillus sp. The tangerine peel was used as raw material, which was previously extracted from the essential oils; the moisture was removed and then passed through the milling. In the hydrolysis of the tangerine peel the diluted acid hydrolysis method was used, the inoculum of Bacillus subtilis and mineral solution was added to then proceed with aerobic fermentation. The biomass was determined by dry cell weight, and to identify the PHA the UV-VIS spectrophotometry method was used by acid digestion and infrared Fourier transform spectrophotometry ATR-FT-IR. The yield of biopolymer production based on biomass was the decisive factor when evaluating production in general; the best production was at a fermentation temperature of 35 ° C and a concentration of initial reducing sugars of 20 g / L